The love song of Miss Queenie Hennessy [compact disc, unabridged] : a novel - Joyce, Rachel (Random House Audio, 2014)
"'The Unlikely Pilgrimage of Harold Fry" followed its unassuming hero on an incredible journey as he traveled the length of England on foot--a journey spurred by a simple letter from his old friend Queenie Hennessy, writing from a hospice to say goodbye. Harold believed that as long as he kept walking, Queenie would live. What he didn't know was that his decision to walk had caused her both alarm and fear. How could she wait? What would she say? Forced to confront the past, Queenie realizes she must write again. In this poignant parallel story to Harold's saga, acclaimed author Rachel Joyce brings Queenie Hennessy's voice into sharp focus. Setting pen to paper, Queenie makes a journey of her own, a journey that is even bigger than Harold's; one word after another, she promises to confess long-buried truths--about her modest childhood, her studies at Oxford, the heartbreak that brought her to Kingsbridge and to loving Harold, her friendship with his son, the solace she has found in a garden by the sea. And, finally, the devastating secret she has kept from Harold for all these years" --